Consumer Legal Remedies Against Developer Default in Binding Agreement for the Sale and Purchase of Flats - Faizzah Rabiatun Ramadani (MultiTech Publisher, 2025)
This study analyzes consumer legal remedies against developer defaults in the Sale and Purchase Agreement (PPJB) of flats. Using normative methods with a legal approach, this study identifies the legal obligations of developers and consumer rights in the context of default. Data is collected from relevant regulations and legal literature to provide in-depth analysis. The findings show that many PPJBs tend to benefit developers, thus putting consumers in a weak position. Consumers can take legal steps through non-litigation dispute resolution or litigation. This research recommends the need for transparency and fairness in agreements to protect consumer rights, as well as the importance of strict law enforcement against violations committed by developers.